(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The construction industry is one of the important sectors of the global economy. Investments in construction help create new jobs in the short term, and in the medium and long term, completed infrastructure facilities reduce transportation costs, improve people’s lives and, most importantly, accelerate economic growth. the construction industry will retain its place as the driving force of the world economy.